The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1094/cchem.1997.74.6.846
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Protein and Starch Studied Through Amyloglucosidase Action

Abstract: The access of amyloglucosidase to the carbohydrate molecule was taken as a measure of interactions occurring among starch, amylose, amylopectin, β‐dextrin and purified gluten, gliadins, high molecular weight glutenin subunits, or bovine serum albumin when they were mixed together and gelatinized before digestion. The most relevant decrease in liberated glucose, denoting coverage of some reaction sites for amyloglucosidase, occurred when gliadins were mixed with the carbohydrates. Other proteins were not as eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 9 publications
1
28
1
Order By: Relevance
“…In conclusion, the study conducted in this work supports our previous hypothesis of an interaction between dextrin and gliadins (9). Moreover, in agreement with Grant et al (39) we found that, despite their low solubility in water, gliadins have hydrophilic character as evidenced by hydrogen-bond formation with water molecules and dextrin.…”
Section: Discussionsupporting
confidence: 93%
“…In conclusion, the study conducted in this work supports our previous hypothesis of an interaction between dextrin and gliadins (9). Moreover, in agreement with Grant et al (39) we found that, despite their low solubility in water, gliadins have hydrophilic character as evidenced by hydrogen-bond formation with water molecules and dextrin.…”
Section: Discussionsupporting
confidence: 93%
“…It has been suggested that the interaction between the starch granules and the surrounding protein matrix may reduce the accessibility of amylolytic enzymes to starch granules in hard wheat (Guerrieri et al, 1997;Peron et al, 2006). It has been suggested that the interaction between the starch granules and the surrounding protein matrix may reduce the accessibility of amylolytic enzymes to starch granules in hard wheat (Guerrieri et al, 1997;Peron et al, 2006).…”
Section: Feed Particle Size and Exogenous Enzymementioning
confidence: 99%
“…The polyacrylamide gel was prepared with a monomer mixture of 8.4YoT and 4.80' oC in 25 mM sodium lactate adjusted to pH 3.1 with NaOH. Electrophoresis was performed as described in Guerrieri et al [29]. The proteins in the gel were fixed for 20 rnin with 100 mL of 12% w/v trichloroacetic acid and stained overnight with 100 mL of 12% w/v trichloroacetic acid plus 10 mL of 5 mg/mL Coomassie Brilliant Blue G-250.…”
Section: Protein Extractionmentioning
confidence: 99%